1996
DOI: 10.1111/j.1471-0528.1996.tb09878.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking during pregnancy: the dose dependence of birthweight deficits

Abstract: Objective To assess whether a simple urine based estimate of relative daily nicotine intake could predict smoking related birthweight deficits more accurately than self‐reported cigarette consumption. Design Active smokers were identified by a simple qualitative colorimetric urine test procedure and their relative nicotine intakes assessed by determining the ratios of the urinary concentrations of nicotine plus its metabolites to creatinine using automated colorimetric methods. Setting A larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 27 publications
1
51
2
Order By: Relevance
“…A recent study reported that passive smoking was associated with reduced birth weight (by 33 g) and 22% increased risk of low birth weight and mortality [19]. Epidemiological studies have shown that the relationship between active heavy smoking and low birth weight is stronger than the passive smoking due to dose-dependent effect [5,7,11,27,37]. In our study, the mean birth weight of the pups in the nicotine A group was lower than in other groups.…”
Section: Secker-walker Et Al Showed That Low Birth Weight In Infantscontrasting
confidence: 65%
“…A recent study reported that passive smoking was associated with reduced birth weight (by 33 g) and 22% increased risk of low birth weight and mortality [19]. Epidemiological studies have shown that the relationship between active heavy smoking and low birth weight is stronger than the passive smoking due to dose-dependent effect [5,7,11,27,37]. In our study, the mean birth weight of the pups in the nicotine A group was lower than in other groups.…”
Section: Secker-walker Et Al Showed That Low Birth Weight In Infantscontrasting
confidence: 65%
“…This observation has implications for the use of cotinine as a biomarker for cigarette smoking during pregnancy. Our data do not affect the validity of cotinine levels as a predictor of pregnancy outcomes, which are based on empirical observations (Mathai et al, 1990;Bardy et al, 1993;Li et al, 1993;Ellard et al, 1996). But our study does indicate that the lower cotinine levels observed in smokers during pregnancy compared with the same individuals before or after pregnancy do not necessarily reflect less smoke exposure.…”
Section: Discussionmentioning
confidence: 60%
“…Among pregnant smokers, maternal levels of cotinine correlate better with outcome measures such as birth weight than the number of cigarettes smoked per day (Haddow et al, 1987;Mathai et al, 1990;Bardy et al, 1993;Li et al, 1993;Ellard et al, 1996;Klebanoff et al, 1998;SeckerWalker et al, 1998). Recently, a study of women during pregnancy and again postpartum found that during pregnancy the median saliva cotinine concentration per cigarette was 3.5 ng/ml versus 9.9 ng/ml when not pregnant (Rebagliato et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…6 This, and a number of studies, have found a closer dose -e¡ect relationship between birthweight de¢cits and nicotine metabolite levels in serum and urine than with self-reported cigarette consumption. 7,8 Serum cotinine concentration at 16 weeks'gestation was also found to have a high positive predictive value for small-for-gestational age deliveries, which was double that for self-reported smoking habit and independent of associated maternal characteristics. 9 This led to the recommendation that Original Article biochemical veri¢cation of self-reported quitting is essential to the evaluation of smoking cessation interventions and may be a useful predictor of poor pregnancy outcome.…”
Section: Introductionmentioning
confidence: 86%